The Politics of Green Transformations - Scoones, Ian; Leach, Melissa; Newell, Peter (Pathways to Sustainability, 2015)
Multiple 'green transformations' are required if humanity is to live sustainably on planet Earth. Recalling past transformations, this book examines what makes the current challenge different, and especially urgent. It examines how green transformations must take place in the context of the particular moments of capitalist development, and in relation to particular alliances. The role of the state is emphasised, both in terms of the type of incentives required to make green transformations politically feasible and the way states must take a developmental role in financing innovation and technology for green transformations. The book also highlights the role of citizens, as innovators, entrepreneurs, green consumers and members of social movements. Green transformations must be both 'top-down', involving elite alliances between states and business, but also 'bottom up', pushed by grassroots innovators and entrepreneurs, and part of wider mobilisations among civil society. The chapters in the book draw on international examples to emphasise how contexts matter in shaping pathways to sustainability Written by experts in the field, this book will be of great interest to researchers and students in environmental studies, international relations, political science, development studies, geography and anthropology, as well as policymakers and practitioners concerned with sustainability.